DELAYED CLAIM PAYMENT AND THE THREAT TO HOSPITAL CASH FLOW UNDER THE NATIONAL HEALTH INSURANCE SCHEME IN INDONESIA - Citra Yuliyanti; Hasbullah Thabrany (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Indonesia commits to ensure health care access for all population through the National Health Insurance (JKN) managed by the BPJS Health. By February 2018, the JKN covered 193 million people (73% of the total population). To ensure health delivery, 2,104 public and private hospitals are contracted by the BPJS and prospective payment using Case-mix Based Group (CBG) that changes hospital managements. Hospitals become more dependent on payments by BPJS. Delay in claim payment will have serious impact on hospital managements. This study aims to identify current practices in timely payment to hospitals and finding factors correlate with delay in payments. Methods: This study used trend analysis of the secondary claim data of BPJS with the total sample of 57,475 bundles of claims. Total claim population was used in this study. In addition, qualitative study via in-depth interview with six informants consisting of members of National Social Security Council, hospital director of three different classes, and BPJS. Results: This study found 60% of claims were paid within one month (N-1) of claim submission, below the target of 100%. There were tendencies of delays in claim settlements since November 2017. Informants believed that late payments were correlated with non-compliance of doctor to complete medical records, incompetence coders, inadequate management information system, and financial condition of BPJS. There were three main problems faced by hospitals as a result of delay in payments: 1) disturbed drug availability, 2) decreased performance of doctors, 3) poorer maintenance of medical equipment. Conclusion: Delayed in claim payments were occurred and led to a threat of decreasing quality of care to patients. The study suggests the government should fix the problems to protect patients from decreasing quality of care. Hospitals should provide reserve funds to protect them from financial hardship when delays occur.